Intentional Mindset Toward Robots—Open Questions and Methodological Challenges - Schellen, Elef; Wykowska, Agnieszka (Frontiers in Robotics and AI, 2019)
Natural and effective interaction with humanoid robots should involve social cognitive mechanisms of the human brain that normally facilitate social interaction between humans. Recent research has indicated that the presence and efficiency of these mechanisms in human-robot interaction (HRI) might be contingent on the adoption of a set of attitudes, mindsets and beliefs concerning the robot’s inner machinery. Current research is investigating the factors that influence these mindsets, and how they affect HRI. This review focuses on a specific mindset, namely the “intentional mindset” in which intentionality is attributed to another agent. More specifically, we focus on the concept of adopting the intentional stance towards robots, i.e., the tendency to predict and explain the robots’ behavior with reference to mental states. We discuss the relationship between adoption of intentional stance and lower-level mechanisms of social cognition, and we provide a critical evaluation of research methods currently employed in this field, highlighting common pitfalls in the measurement of attitudes and mindsets.